(untitled) (Proceedings of the International Conference on Education, 2025)
This exploratory study examines the current best practices in teaching Mandarin Chinese in an online environment in Trinidad & Tobago, a context where online language learning is relatively new and growing in importance. The growing cultural and economic connections between China and Trinidad & Tobago have increased the demand for Mandarin language skills, particularly in the virtual classroom. This study focuses on identifying effective strategies for engaging learners in a digital environment, integrating culturally relevant content, and utilising technology to enhance learning outcomes. The methodology involved surveying fifty (50) adult learners who studied Mandarin online for at least one semester (52 contact hours) at the Centre for Language Learning, The University of the West Indies, St. Augustine campus. Despite some challenges inherent to virtual learning such as connectivity issues, students expressed satisfaction with their classes due to effective practices adopted by their instructors. These included the use of ICT tools and the incorporation of culturally relevant material, which bridged the gap between Chinese and Caribbean contexts. This study intends to provide insights into the successful application of online teaching methods for Mandarin Chinese in Trinidad & Tobago. Although the study is limited by its small sample size, its findings offer recommendations for improving student engagement, autonomy, and proficiency in foreign language education across the Caribbean.